Homeland Defense: Another Nail in the Coffin for Posse Comitatus - Nathan Canestaro (Washington University Journal of Law & Policy, 2003)
Since its enactment in 1878, the Posse Comitatus Act (“PCA”) has upheld a basic value of American democracy—the principle that the military cannot enforce civilian law. This principle, derived from a long tradition of antimilitarism in English common law, represents the “traditional and strong resistance of Americans to any military intrusion into civilian affairs.” This Article will prove that the “War on Terrorism” will undermine the PCA. The “War on Drugs” has already eroded the PCA, but the “War on Terrorism” could be fatal to it. First, this Article will examine the roots of the principle of posse comitatus in English Common Law, and in the context of Colonial America and the post-Reconstruction period. This Article will establish that a separation of the civil and military spheres, specifically by prohibiting the military’s enforcement of civil law, is a fundamental value upon which the United States was founded. It will show how this prohibition has been slowly eroding since early in this nation’s history. Focusing on the civil abuses of posse comitatus during the Reconstruction period will demonstrate the consequences of unchecked domestic military power. Next, this Article will turn to the 1981 and 1988 Drug War amendments to the PCA to show that Congress has demonstrated its intent to levy the military’s resources against society’s problems, even over the DoD’s objections to extend their duties beyond their role as the nation’s “warfighter.” This Article will then examine each of the exceptions to the PCA to prove that substantial exceptions have seriously weakened it. Building on narrow judicial interpretations of the PCA, Congress has responded to modern national security threats such as drugs, terrorism, and weapons of mass destruction by giving the military a substantial support role. Beginning with the Wounded Knee standoff of 1973, the amount of military assistance that the PCA permits has risen dramatically. Meanwhile, the courts have been extremely reluctant to enforce violations to expand its scope beyond criminal sanctions. Finally, this Article will analyze the military’s growing role in homeland defense, and explore the consequences of the decline of posse comitatus.
Keywords: Counterterrorism; United States -- Armed Forces; Law enforcement; Antiterrorism measures; Military law; Military policy; Posse Comitatus Act; United States